2005
DOI: 10.1158/1078-0432.ccr-04-2047
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Inhibition of Methylenetetrahydrofolate Reductase Reduces Cancer Cell Survival In vitro and Tumor Growth In vivo

Abstract: Purpose: Many cancer lines are methionine dependent and decrease proliferation when methionine supply is limited. Methylenetetrahydrofolate reductase (MTHFR) generates the folate derivative for homocysteine remethylation to methionine. We investigated the effect of antisensemediated inhibition of MTHFR on survival of human cancer cells.Experimental Design: We examined the in vitro and in vivo anticancer effects of a combination of MTHFR antisense and standard cytotoxic drugs.Results: Specific antisense against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Such protective role of the polymorphism was what we observed from Asian studies. Moreover, Stankova suggested antisense inhibition of MTHFR could reduce cancer cell survival in vitro and tumor growth in vivo (Stankova et al, 2005), and such inhibition produced similar effect as the polymorphism. But why did opposite effect exist in studies from Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Such protective role of the polymorphism was what we observed from Asian studies. Moreover, Stankova suggested antisense inhibition of MTHFR could reduce cancer cell survival in vitro and tumor growth in vivo (Stankova et al, 2005), and such inhibition produced similar effect as the polymorphism. But why did opposite effect exist in studies from Europe.…”
Section: Discussionmentioning
confidence: 99%
“…25 Antisense against MTHFR showed significant inhibitory effects in growth of human colon, lung, breast, prostate and neuroblastoma tumor cells in vitro and it was suggested that inhibition of MTHFR may be a novel anticancer approach. 26 Global genomic hypomethylation is associated with malignant lymphoproliferative diseases. 27 Aberrant DNA methylation of promoter-associated CpG islands is very common in hematological malignancies 28 including adult acute lymphoblastic leukemia 29,30 and cutaneous T-cell lymphoma, 31 the profile of CpG island hypermethylation in hematologic malignancies could be an epigenetic signature unique for each subtype of leukemia or lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an antisense sequence against MTHFR mediated the downregulation of gene expression and inhibited tumour growth in vivo and in vitro. 4,17 Backus et al 18 reported that cancer cell lines cultured with high concentrations of folate showed higher expression and catalytic activity of TS protein than those grown at low folate levels. The findings of the present investigation, however, suggest that MTHFR polymorphism does not increase TS gene expression.…”
Section: Discussionmentioning
confidence: 99%